E-commerce platform financing versus trade credit financing: Financing mode selection for online retailer considering live-stream selling in China - Huang, Shuai; Du, Bingzhi; Fan, Zhi-Ping; Liu, Zhixi (Frontiers in Psychology, 2023)
Introduction The rise of live-stream selling has made the e-commerce platform attractive to many small and medium-sized retailers that are often faced with capital constraints. The choice between the e-commerce platform financing (EPF) and trade credit financing (TCF) for the capital-constrained e-retailers engaging in live-stream selling is particularly important problem. Methods This paper considers a supply chain made up of a manufacturer, an e-commerce platform that offers live-stream selling service to consumers and an online retailer with capital constraint. We, respectively, investigate the optimal decisions of the supply chain enterprises under EPF and TCF modes based on Stackelberg game models and optimization theories. Results We compare the profits of supply chain firms under different cases and obtain some important conclusions through theoretical and numerical analysis. Discussion First, when the e-commerce platform’s commission rate is low enough, the retailer’s ordering quantity is, under EPF mode, greater than that evidenced without capital constraint. In addition, when the retailer’s marginal profit is high and the e-commerce platform’s commission rate is low, the online retailer should choose EPF mode; in other instances, TCF is its optimal choice. Second, the e-commerce platform can obtain the highest profit under EPF mode, while TCF mode will bring the highest profit to the manufacturer. Third, when the platform’s commission rate is below a certain threshold, the profit of the entire supply chain under EPF mode is larger than that of well-funded supply chain, but TCF mode cannot. Finally, we also find there exists the access threshold about the live-stream selling. Only when the commission rate is relatively high, the e-commerce platform should offers live-stream service to consumers and the live-stream investment is the highest under EPF mode.